Influenza pathogenesis: mechanisms of modulation by agent proteins - M. Yu. Shchelkanov; A. F. Popov; A. I. Simakova; I. V. Zenin; E. S. Proshina; I. M. Kirillov; K. A. Dmitrenko; D. V. Shevchuk (Журнал инфектологии)
Modern concepts of the influence of the proteins from viruses-etiological agents of flu – Influenzavirus A, B and C (Orthomyxoviridae) – on the development of different elements of the main disease pathogenesis are analyzed in the review. In particular, the short description of life cycle of Influenza viruses is alleguered with special attention to those its stages which are capable to modulate pathogenetic mechanisms. The interrelation between the structure of hemagglutinin receptor-binding site and virus tropism as well as the influence of the receptor-destroying virus proteins on this phenomenon is described. The mechanism of suppression of interferon production in the infected cell by virus NS1 protein is presented. The induction of apoptosis by nonstructural PB1-F2 protein of Influenza A virusis described.